Qualitative physical assessment on the effects of salt on potential hydrogels used in nanoparticle drug delivery - Abd Moulud, Ummi Nadiahtulnajiah; Mohamed Suffian, Izzat Fahimuddin; Zakaria, Siti Fatimah; Hamzah, Nurasyikin; Che Othman, Siti Fairuz (IIUM Press, 2022)
The prevalence of oral cancer cases worldwide has urged scientists to revise topical drug formulations meant for oral application improving drug locality. This alternative treatment helps to minimise the side effects from the current available treatment. The physicochemical properties of the material need to be assessed when designing a new topical drug. Therefore, this paper aims in developing formulation and characterise hydrogels with the addition of different salt concentrations. In this project, the hydrogels studied are iota-carrageenan and kappa-carrageenan. As salt is the common ingredient used in drug formulation, the effects of salt on the physical properties of carrageenan are studied. Each concentration of the carrageenan is formulated with four different concentrations of salt at 0.5%, 1.0%, 1.5%, and 2.0%. The pH of the solution is maintained at pH 7. The results show that both concentrations of kappa-carrageenan are not suitable to be used as a carrier for nano-topical drugs due to their hard and rigid texture. Based on the physical properties, the suitable formulation for nano-matrix would be the 0.5% iota-carrageenan added with 1.5% and 2.0% NaCl, as well as the 1.0% iota-carrageenan added with 0.5% NaCl.